The Auction System in Motorcycle Arisan Practices: A Review of Minister of Finance Regulation Number 122 of 2023 on Auction Implementation Guidelines - Damainingrum, Vania Diva; Labibah, Hanin Alya' (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
Auction in motorcycle arisan are organized by a business entity without interference from the government with the aim of selling goods, namely motorcycles. Motorcycle arisan adopts an auction system to be used as the determination of the winner of the arisan. This study aims to determine the implementation of auction at motorcycle arisan in terms of the regulation of the minister of finance regarding auction implementation guidelines. The data used was obtained through literature studies related to the issue. This type of research is normative legal research using a legal approach and a conceptual approach. In this study, it can be concluded that the auction carried out at the motorcycle arisan is actually used only for business purposes for the arisan organizers, where the auction team is formed independently by the arisan organizers without an Auction Official. Judging from the purposes of motorcycle arisan which is the sale of motorcycles with an auction system, then it is included in the category of voluntary auctions where the implementation stage is regulated in the ministerial regulation, so that business entities as the organizers of motorcycle arisan with an auction system must carried out auction activities to be adjusted to the voluntary auction procedures that have been regulated in laws and regulations.